A novel application of ultrasonic Lamb waves: studying adhesive effects on the inspection of coating debonding in a three-layer waveguide. Issue 6 (2nd November 2021) - Mehrabi, Mohammad; Soorgee, Mohammad Hossein; Habibi, Hossein; Kappatos, Vassilios
ABSTRACT: In this research, a thorough experimental and numerical study is conducted to investigate a novel application of the ultrasonic Lamb waves which is its capability to detect the coating disbond in a double-layer waveguide (aluminium-adhesive) and a triple-layer waveguide (aluminium-adhesive-coating). The experimental tests are set up and implemented to evaluate how the attenuation of Lamb waves is affected by the adhesive bonding beside the contribution of the coating layer to the behaviour of Lamb waves. In the presence of additive white Gaussian noise (AWGN), a range of important indices including energy index (EI), amplitude index (AI), pulse width index (PWI), and the time of flight index (ToFI) are worked out in association with the disbond length. It is inferred that a) even in the very noisy environment of 0 dB SNR, the Lamb waves are effectively able to identify debonding defects particularly using the EI, giving sensitivity rates 105% and 30% for triple-layer and double-layer, respectively; b) the contribution of adhesive to the absorption of the guided wave energy is 30%, 40%, and 50% in EI, AI, and PWI, respectively, corroborating the value of the features to distinguish the debonding between each layer of bonded structures.